Pengentasan Kemiskinan dan Kesejahteraan Rakyat: Kebijakan Politik Perempuan Sherly Tjoanda di Maluku Utara - Mufidah Aufa Nur Husna; Nacwa Aisyilla Naisyila; Zafira Adzra Daffany; Tiara Rahma Aulia; Aniqotul Ummah; Hendika Dwinanda Wicaksana (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study aims to analyze the political leadership of Sherly Tjoanda as the Governor of North Maluku in addressing poverty alleviation and improving public welfare. The study is motivated by the low representation of women in Indonesian politics despite the implementation of affirmative action policies, as well as the complex development challenges in North Maluku, where rapid economic growth driven by the mining sector has not been accompanied by equitable welfare distribution. This research employs a qualitative approach using a single case study design. Secondary data were collected from government documents, Statistics Indonesia (BPS) reports, the Regional Medium-Term Development Plan (RPJMD), official speeches, and relevant media publications. Data were analyzed using the Miles and Huberman interactive model, supported by thematic analysis based on transformational leadership theory, gender leadership theory, feminist political economy, and media framing analysis. The findings indicate that Sherly Tjoanda's leadership adopts a participatory, collaborative, and welfare-oriented approach through policies focusing on rural infrastructure development, the empowerment of agriculture, fisheries, tourism, and the development of Sofifi as the provincial administrative center. Although North Maluku has experienced remarkable economic growth due to the downstream nickel industry, the equitable distribution of welfare remains a significant challenge. This study concludes that women's political leadership is capable of producing inclusive, responsive, and socially oriented public policies that contribute to more equitable regional development.